Transisi Data dan Informasi dalam Pengembangan Ilmu Pengetahuan - Mulyadi Mulyadi (IAIN Ponorogo, 2018)
Data transition is a transition of data until it becomes wisdom. Why the transition of data, information, knowledge and wisdom is interesting to study, because science can not only be understood as the result of static scientific and legal theory, but science is the process, activity and ability developed by scientists to finally become wisdom. The main problem that occurs is the public especially the world of education more presented with various results of science that is ready and ready to use, without seeing the process of work and science activities.On the basis of this, we must be able to build the character of a scientist, the person who is always dissatisfied and always restless questioning and questioning everything, is critical of the results of knowledge that has been developed by the previous people specialized in the field of library science. A knowledge or information that will be presented to users in the library, must first be verified in advance where the data source and how interpret it to be understood by the user so the information received is completely valid and does not cause anxiety and debate. The method used in data processing by looking at relations (relations), then designed with a pattern (pattern) particular, and eventually become principles (principles) to be done and implemented together. Thus it can be concluded that to make the data into a knowledge and ultimately a principle that can be implemented by many people has become a necessity for information managers have a soul as a true scientist who does not have partiality so that science really stands above truth.